Competency development through empowerment: A model for millennial vegetable farmers in West Java Highlands - Pradiana, Wida; Suwarto; Sapja Anantanyu; Suminah (Research Journal in Advanced Humanities, 2025)
The decreasing interest in agriculture among younger generations threatens Indonesia’s food security, particularly as food demand rises. Enhancing millennial farmers’ competencies is essential due to their limited experience and formal education. This study develops an empowerment model aimed at increasing competencies among millennial vegetable farmers in West Java. Using a cross-sectional survey and Structural Equation Modeling (SEM) with AMOS, this research examined how factors such as environmental and institutional support, participation, and motivation influence competencies. Model fit was confirmed with indices including Comparative Fit Index (CFI) = 0.936, Goodness-of-Fit Index (GFI) = 0.920, Adjusted Goodness-of-Fit Index (AGFI) = 0.900, Tucker-Lewis Index (TLI) = 0.921, and Root Mean Square Error of Approximation (RMSEA) = 0.047. Findings highlight that nearest environment support and intrinsic motivation are key factors shaping farmers’ perceptions and competencies, while institutional support significantly affects perceptions but has a less direct influence on competence. Active participation and motivation were positively correlated with enhanced competence. This empowerment model underscores the importance of combining institutional support with strategies to increase motivation and engagement, offering actionable insights for policymakers and practitioners to improve the effectiveness and sustainability of millennial farmers in vegetable farming.